2015
DOI: 10.3897/zookeys.515.9390
|View full text |Cite
|
Sign up to set email alerts
|

NEIGHBOUR-IN: Image processing software for spatial analysis of animal grouping

Abstract: Animal grouping is a very complex process that occurs in many species, involving many individuals under the influence of different mechanisms. To investigate this process, we have created an image processing software, called NEIGHBOUR-IN, designed to analyse individuals’ coordinates belonging to up to three different groups. The software also includes statistical analysis and indexes to discriminate aggregates based on spatial localisation of individuals and their neighbours. After the description of the softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Several marking techniques also exist to follow individuals, which can facilitate the monitoring of species during experiments (Hagler & Jackson, ), and such technical approaches provide a good working basis for further experimentation on mixed‐species groups. Moreover, various theories, mathematical models and metrics have been developed in the context of aggregation and could be applied or adapted to mixed‐species groups (for metrics, see Ives, ; Sauphanor & Sureau, ; Everaerts et al ., or Caubet & Richard, ; for models, see Deneubourg et al ., or Nicolis et al ., ). However, models of the cooperation–competition phenomenon still need to be established for mixed‐species groups, but the required experimental data are currently lacking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several marking techniques also exist to follow individuals, which can facilitate the monitoring of species during experiments (Hagler & Jackson, ), and such technical approaches provide a good working basis for further experimentation on mixed‐species groups. Moreover, various theories, mathematical models and metrics have been developed in the context of aggregation and could be applied or adapted to mixed‐species groups (for metrics, see Ives, ; Sauphanor & Sureau, ; Everaerts et al ., or Caubet & Richard, ; for models, see Deneubourg et al ., or Nicolis et al ., ). However, models of the cooperation–competition phenomenon still need to be established for mixed‐species groups, but the required experimental data are currently lacking.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Hassall et al . () also demonstrated that two species of woodlice, Porcellio scaber and Armadillidium vulgare , can clump together (see also Caubet & Richard, ). Consistent with the Allee effect, these authors found that at low densities, mixed‐species groups promote population growth that results in positive fitness consequences (higher growth rates and survivorship of group members) (Hassall et al ., ).…”
Section: Benefitsmentioning
confidence: 88%
“…Many studies devoted to heterospecific interactions have been reported, from unicellular and social amoeba 34 to woodlices 35 , ants 36 37 and mammals 2 20 38 . For example, some species of Triatominae are attracted to the chemical signals left from individuals of the same and of different species 39 .…”
Section: Discussionmentioning
confidence: 99%
“…It has made remarkable achievements in the fields of transportation, medicine, communication, geology, and so on. This paper mainly studies the related content of image processing technology in the field of transportation, including the identification of moving objects in the traffic video image, the prediction of moving objects' driving track, and the application in the intelligent transportation system [20,21].…”
Section: Statistical Distribution Of Traffic Flowmentioning
confidence: 99%